Investigation of Microbiological, Chemical, Sensory and Nutritional Properties of Gravlax Prepared from Catfish - Yıldız, PO; Kızıloğlu, N (Journal of the Hellenic Veterinary Medical Society, 2025)
Gravlax, a traditional Scandinavian dish made by curing fish with salt, sugar, and dill, was prepared using catfish (Silurus glanis) to evaluate its microbiological, chemical, sensory, and nutritional properties. The samples were divided into 3 groups: vacuum-packed fresh fish meat (A), standard gravlax applied (B), gravlax with different additives (additional coriander, celery, grated carrots, lemon and beetroot) (C). While the protein, lipid, ash, carbohydrate contents of gravlax-treated samples were found to be higher compared to fresh fish meat, decreases in moisture content were observed. The growth of bacterial was slower in gravlax samples. Increases in TBARS, TVB-N values were observed in parallel with storage, and the effect of storage time was also found to be significant (p<0.01). Group C was the most liked group in terms of all sensory parameters. All these analyzes concluded that the gravlax process had positive effects on the quality parameters of the samples and also increased the shelf life of the product.